Pulmonary Manifestations plain rabbit transported up - Mori CHávez, P. (1936)
As we have seen there is a prancing made ​​in the study of the lungs of rabbits transported to the high level, and they do not reveal changes that indicate an influence of oxygen depletion on that body, which has great importance for us as we what we said in relation to the pathogenesis of altitude sickness, for suggesting that under the new peristasia, regulatory mechanisms, ie compensating, balanced act in the rabbit, which is not true in the guinea pig, which reveals undoubted mode or irritability particularly susceptibility against multiple stimuli including the height triggers significant disruption verified, although in varying degrees, with marked evidence at all, as we have shown in our previous work. This irritability or susceptibility of species (guinea pig caviai spice) conditions as in our concept fundamentally pathogenesis "mountain sickness", as well as in man is the susceptibility or individual irritability that makes a more labile than others to that suffer badly. The structure of the lung of the rabbit, as we have explained, is extremely similar to that of the guinea pig, then one might assume, a priori, that their modality reaction against different stimuli were similar, which does not occur, thus indicating that the structure of body, being so important, is not sufficient by itself to explain his reaction mode, and to the pathological fact springs into our minds, the possibility of intervention by Total reguladoires mechanism therefore neuro-humoral suffering deviations or disturbances in their shape and capacity of action.